Nitric oxide‐enhanced Shiga toxin production was regulated by Fur and RecA in enterohemorrhagic Escherichia coli O157. Issue 4 (15th March 2017) - Ichimura, Kimitoshi; Shimizu, Takeshi; Matsumoto, Akio; Hirai, Shinichiro; Yokoyama, Eiji; Takeuchi, Hiroki; Yahiro, Kinnosuke; Noda, Masatoshi
Abstract: Enterohemorrhagic Escherichia coli (EHEC) produces Shiga toxin 1 (Stx1) and Shiga toxin 2 (Stx2). Nitric oxide (NO), which acts as an antimicrobial defense molecule, was found to enhance the production of Stx1 and Stx2 in EHEC under anaerobic conditions. Although EHEC O157 has two types of anaerobic NO reductase genes, an intact norV and a deleted norV, in the deleted norV ‐type EHEC, a high concentration of NO (12–29 μmol/L, maximum steady‐state concentration) is required for enhanced Stx1 production and a low concentration of NO ( 12 μmol/L, maximum steady‐state concentration) is sufficient for enhanced Stx2 production under anaerobic conditions. These results suggested that different concentration thresholds of NO elicit a discrete set of Stx1 and Stx2 production pathways. Moreover, the enhancement of Shiga toxin production in the intact norV ‐type EHEC required treatment with a higher concentration of NO than was required for enhancement of Shiga toxin production in the deleted norV ‐type EHEC, suggesting that the specific NorV type plays an important role in the level of enhancement of Shiga toxin production in response to NO. Finally, Fur derepression and RecA activation in EHEC were shown to participate in the NO‐enhanced Stx1 and Stx2 production, respectively. Abstract : Enterohemorrhagic Escherichia coli (EHEC) produces Stx1 and Stx2. A high concentration of nitric oxide (NO) enhanced Stx1 production in EHEC by Fur derepression under anaerobic conditions. A low concentration of NO enhanced Stx2 production by RecA activation. The specific NorV (NO reductase) type in EHEC plays an important role in the level of enhancement of Shiga toxin production in response to NO.